Impacts of ocean warming and acidification on predator-prey interactions in the intertidal zone: A research weaving approach - Guarizo, Matheus [UNESP]; Pardo, Juan C.F.; De Grande, Fernando Rafael; Vinagre, Catarina; Costa, Tânia Marcia [UNESP] (Elsevier, 2023)
The effect of ocean warming and acidification on predator-prey interactions in the intertidal zone is a topic of growing concern for the scientific community. In this review, we aim to describe how scientists have explored the topic via research weaving, a combination of a systematic review, and a bibliometric approach. We assess articles published in the last decade exploring the impact of both stressors on predation in the intertidal zone, via experimental or observational techniques. Several methods were used to delve into how climate change-induced stress affected intertidal predation, as the study design leaned toward single-based driver trials to the detriment of a multi-driver approach. Mollusks, echinoderms, and crustaceans have been extensively used as model organisms, with little published data on other invertebrates, vertebrates, and algae taxa. Moreover, there is a strong web of co-authoring across institutions and countries from the Northern Hemisphere, that can skew our understanding towards temperate environments. Therefore, institutions and countries should increase participation in the southern hemisphere networking, assessing the problems under a global outlook. Our review also addresses the various impacts of ocean acidification, warming, or their interaction with predation-related variables, affecting organisms from the genetic to a broader ecological scope, such as animal behaviour or interspecific interactions. Finally, we argue that the numerous synonyms used in keywording articles in the field, possibly hurting future reviews in the area, as we provide different keyword standardizations. Our findings can help guide upcoming approaches to the topic by assessing what has been already done and revealing gaps in emerging themes, like a strong skew towards single-driver (specially acidification) lab experiments of northern hemisphere organisms and a lack of field multi-stressor experiments.
Keywords: Climate Change; Coastal Environment; Ecological Interactions; Research Weaving